Effect of hydration on molecular dynamics and structure in chitosan films. (December 2016) - Madeleine-Perdrillat, Claire; Karbowiak, Thomas; Debeaufort, Frédéric; Delmotte, Luc; Vaulot, Cyril; Champion, Dominique
Abstract: Water-mediated modifications in chitosan films were investigated from both molecular mobility and structure perspectives. Chitosan films, prepared by the solvent casting method in acetic acid medium, were exposed to relative humidity ranging from 11% to 92% at 25 °C. This work reveals that chitosan film exhibits a different structure below and above a water content of around 15% (w/w wet basis). A marked increase in mobility was evidenced at this point from proton relaxation and paramagnetic probe rotational mobility. The influence of such mobility modification was further studied by differential scanning calorimetry but no classical plasticizing effect of the water on the glass transition of chitosan was detected. The same singular point was observed when the water content increased, but no regular decrease of the Tg values was noticed. However, after heating above 80 °C, the polymer film lost its initial characteristics, consecutively to acetic acid release and structural reorganization of the polymer network. It gave rise to the presence in such chitosan films of two distinct amorphous domains associated to a wide change in the baseline due to the glass transition phenomenon. Such instability originates from heterogeneities at the molecular scale. Graphical abstract: Highlights: Water-mediated modifications in chitosan films. Two different behaviours of both sides of ∼15% water content (w/w wet basis). Impact of structural changes on molecular mobility.